Genomic insights into growth and its disorders: an update. Issue 1 (February 2016) - de Bruin, Christiaan; Dauber, Andrew
Abstract : Purpose of review: This article provides an update of the most striking new developments in the field of growth genetics over the past 12 months. Recent findings: A number of large genome-wide association studies have identified new genetic loci and pathways associated to human growth and adult height as well as related traits and comorbidities. New genetic causes of primordial dwarfism and several short stature syndromes have been elucidated. Moreover, a breakthrough finding of Xq26 microduplications as a cause of pituitary gigantism was made. Several new developments in imprinted growth-related genes (including the first human mutation in insulin-like growth factor II) and novel insights into the epigenetic regulation of growth have been reported. Summary: Genomic investigations continue to provide new insights into the genetic basis of human growth as well as its disorders.